THE USE OF ELLIPSIS IN HINGLISH SHORT MOVIE - Sinta Fitri Safwarika; Nai Supartini Atmawidjaja (IKIP Siliwangi, 2019)
In discourse features, including cohesion, there is an ellipsis. Ellipsis is one of the features to make communication more effective especially in written. Ellipsis exist in three kinds there are a nominal ellipsis, verbal ellipsis, and clausal ellipsis. Based on that problem, the researcher wants to investigate what are the ellipsis elements used, implemented and how are the ellipsis expressed in Hinglish Short Movie which have title “Divorce” . In order that can give critical analyze, describe the ellipsis elements and the interpretation of the ellipsis in the dialogues of that movie itself and practically it gives contribution for the teachers, students, researcher, education and other researchers. The technique used by the researcher was documentation by watching “Divorce” Hinglish with analysis of the dialogues from the movie. From the data that have been analyzed, it was found that there were three types of ellipsis elements that occurred in the analysis of ellipsis in “Divorce” Hinglish Movie. The most frequent types were verbal ellipsis occurred 3 times clausal and nominal ellipsis occurred once of a time both of them. Verbal ellipsis was the most productive types.Keywords: Discourse, Cohesion, Ellipsis, nominal ellipsis, verbal ellipsis, clausal ellipsis